Modulation of Innate Immune-Related Genes and Glucocorticoid Synthesis in Gnotobiotic Full-Sibling European Sea Bass (Dicentrarchus labrax) Larvae Challenged With Vibrio anguillarum - Reyes-López, Felipe E.; Aerts, Johan; Vallejos-Vidal, Eva; Ampe, Bart; Dierckens, Kristof; Tort, Lluis; Bossier, Peter (Frontiers in Immunology, 2018)
Although several efforts have been made to describe the immunoendocrine interaction in fish, there are no studies to date focusing on the characterization of the immune response and glucocorticoid synthesis using the host-pathogen interaction on larval stage as a model. Therefore, the aim of this study was to evaluate the glucocorticoid synthesis and the modulation of innate immune-related genes in European sea bass (Dicentrarchus labrax) larvae challenged with Vibrio anguillarum. For this purpose, we challenged by bath full-sibling gnotobiotic sea bass larvae, as an early developmental stage model of study, with 107 CFU mL−1 of V. anguillarum strain HI 610 on day 5 post hatching (dph). The mortality was monitored up to the end of the experiment (120 hours post-challenge, hpc). While no variations were registered in non-challenged larvae maintained under gnotobiotic conditions (93.20 % survival at 120 hpc), in the challenged group a constant and sustained mortality was observed from 36 hpc onwards, dropping to 18.31 % survival at 120 hpc. Expression analysis of innate immunity-related genes and glucocorticoid quantification were carried out in single larvae. The expression of lysozyme, transferrin, and il-10 differentially increased at 120 hpc together with a marked upregulation of the pro-inflammatory cytokines (il-1β and il-8) and hepcidin, suggesting a late activation of defense mechanisms against V. anguillarum. Importantly, this response coincided with the lowest survival observed in challenged groups. On the other hand, an increase of cortisol, cortisone and 20β-dihydrocortisone was observed at 120 hpc as well. Therefore, the increase in markers associated with glucocorticoid synthesis together with the upregulation of genes associated with the anti-inflammatory response suggests that in larvae infected with V. anguillarum a pro-inflammatory response at systemic level takes place, which then leads to the participation of other physiological mechanisms at systemic level in order to counteract the effect and the consequences of such response. However, this late systemic response could be related to the previous high mortality observed in sea bass larvae challenged with V. anguillarum.